Dual-fuel combustion of hydrocarbon fuel droplets in lean, premixed methane/oxidizer mixtures in a rapid compression machine - Gould, Colin M., author; Marchese, Anthony, advisor; Windom, Bret, committee member; Dandy, David, committee member (Colorado State University. Libraries, 2018)
The combustion of two fuels with disparate reactivity (dual-fuel) has been shown to be an effective method for increasing fuel efficiency and reducing both fuel costs and pollutant formation in internal combustion engines. Due to recent decreases in the price of natural gas, the incentive has grown to operate engines in dual-fuel mode, where some amount of diesel is substituted with natural gas. Since natural gas is expected to remain less expensive on a per-unit-energy basis than diesel fuel for the foreseeable future, it will continue to be economically advantageous to maximize the substitution percentage of natural gas in dual-fuel engines. However, at higher natural gas substitution percentages, uncontrolled fast combustion (i.e. engine knock) can occur, which limits the load of the engine and can shorten the lifetime of engine components. Emission of unburned methane has also been shown to increase with increasing natural gas substitution percentage. Previous detailed computational engine modeling at CSU with reduced chemical kinetics and simplified spray models has captured these effects but little data are available to validate chemistry and spray models at engine-relevant conditions. In this study, a rapid compression machine (RCM) was used as a platform to provide a high-temperature/high-pressure environment to better understand the thermodynamic, transport and chemical kinetic phenomena of dual-fuel combustion. The RCM was modified to perform evaporation and combustion experiments on single n-alkane fuel droplets in gaseous inert, O2/inert and O2/CH4/inert environments. Droplet evaporation experiments were performed on C5 to C12 n-alkane droplets in inert gas to measure droplet evaporation rates at near supercritical and supercritical conditions (18 bar < P < 35 bar; 450 K < T < 850 K). The Dual-fuel droplet evaporation and combustion experiments were studied using pressure data and images collected a Schlieren optical system. In the combustion experiments, ignition delay of heptane/O2/inert was quantified at elevated pressure and temperature (27 bar < P < 38 bar; 844 K < T < 1251 K). In addition, the process of dual-fuel combustion was captured, showing two distinct ignition events.